The effect of empathy intervention and VR exergames on social anxiety in left-behind children - Xiao, Zhiyan; Peng, Dianhui; Lu, Chunxia; Zhuang, Xueqin (Frontiers in Psychology, 2025)
IntroductionThis study investigated the comparative effectiveness of empathy intervention and virtual-reality exergames in reducing social anxiety among rural left-behind children (RLBC) in China.MethodsSixty RLBC from Huangdu Primary School in Shaodong City, Hunan Province were randomly assigned to three groups—the Empathy Intervention Group (EG), the VR Exergames Group (VG), and the Control Group (CG)—with 20 participants each. The Children’s Social Anxiety Scale (CSAS) was administered at baseline (T0), post-intervention (T1, Week 12), and 4-week follow-up (T2).ResultsResults showed no baseline differences between groups (P > 0.05). At T1, both EG and VG demonstrated significant reductions in overall CSAS and subscale scores, with VG outperforming EG. By T2, VG maintained significant gains (P < 0.05), while EG exhibited delayed but sustained improvement (P < 0.05), though no significant change occurred between T1 and T2 (P > 0.05). The control group remained stable throughout (P > 0.05).DiscussionThese findings suggest VR exergames yield stronger immediate effects, while empathy interventions show gradual efficacy, highlighting distinct therapeutic trajectories for RLBC’s social anxiety management.